Respuesta :

Answer:

Thus, f and g are inverse functions

Step-by-step explanation:

Inverse Functions

If two functions f(x) and g(x) are inverses, then it follows that:

[tex]f\circ g(x)=x[/tex]

Or:

[tex]g\circ f(x)=x[/tex]

We are given

[tex]\displaystyle f(x)=\frac{1}{4}x-6[/tex]

[tex]g(x)=4x+24[/tex]

Let's test if they are inverse functions:

[tex]f\circ g(x)=\frac{1}{4}(4x+24)-6[/tex]

Simplifying:

[tex]f\circ g(x)=x+6-6=x[/tex]

Now find:

[tex]\displaystyle g\circ f(x)=4\left(\frac{1}{4}x-6\right)+24[/tex]

Operating:

[tex]\displaystyle g\circ f(x)=x-24+24=x[/tex]

Thus, f and g are inverse functions

ACCESS MORE